Campus Climate Survey on Sexual Assault and Sexual Misconduct, 2014-2019 ([Verlag nicht ermittelbar], 2020)
In 2018, the Association of American Universities (AAU) assembled 33 schools to participate in the spring of 2019 as a follow-up to the 2015 survey. For those who participated in the 2015 AAU survey and others who had implemented the AAU survey on their own, the 2019 survey provided a means to track trends for key types of victimization and climate outcomes. The AAU sought to examine the prevalence of and assess the campus climate regarding sexual assault and misconduct at colleges and universities. The goal of these surveys was to gather as much information about the issue as possible to help inform member schools as they create policies and strategies to combat sexual assault and misconduct on their campuses. The study reported on the following research questions: How extensive is nonconsensual sexual contact? How extensive are sexual harassment, stalking, and intimate partner violence (IPV)? What are students' experiences with campus programs and resources? What are students' perceptions and experiences related to sexual assault and other sexual misconduct? Have the prevalence, knowledge, and perceptions of risk for sexual assault or misconduct changed since 2015? A total of 181,752 students out of a total student sample size of 830,936 completed the survey. Within this sample, there were 108,221 undergraduate respondents and 73,531 graduate and professional respondents; 95,975 respondents from private institutions and 85,777 respondents from public institutions. Demographic variables include age, year in school/program, year enrolled, race, citizenship, gender, sexual orientation, marital status, and disability status. This study includes 3 data files. The first two files are respondent-level and incident-level data, respectively. The respondent-level file (DS1) contains all the survey data; this includes the survey items, derived variables, weight variables, and ID variables. The incident-level file (DS2) contains only a subset of the survey items; these include the Detail Incident Form (DIF) items (variables that start with 'GA'), the COMPLETE indicator, derived variables related to the DIF, ID, and weight variables. A third SAS data file (DS3) is provided that has the replicate weight factors for use with survey procedures that utilize replicate weights for variance estimation.